PENTINGNYA PERLINDUNGAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK - Yudhianto, Haris (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Electronic transactions have become an integral part of modern life. The convenience and speed offered by electronic transactions are not balanced with adequate legal protection for consumers. This study aims to analyze the legal framework that applies in protecting consumers in electronic transactions in Indonesia, In addition, this research will also discuss business practices that are detrimental to consumers in electronic transactions and efforts that can be made to increase consumer awareness